Comportamento de chamamento e evidência de feromônio sexual em Atheloca subrufella (Hulst) (Lepidoptera: Phycitidae) - Nascimento, Eduardo Silva (2013)
The coconut moth, Atheloca subrufella (Hulst) (Lepidoptera: Phycitidae), is considered an important pest of coconut crop, especially in the Northeast of Brazil, which holds more than 70% of coconut production in the country. Its control is difficult because the caterpillars develop inside the flowers and fruits of the coconut palm, limiting the action of chemical agents. Thus, the use of pheromone for this insect management becomes quite promising. The objectives of this study were to describe the calling behavior of A. subrufella females and to verify the function of the pheromones involved in this process. The calling position, pattern and frequency of calling were evaluated. Female pheromone glands extracts were obtained and male and female volatiles were also collected by an aeration process, and were analyzed on a GC/MS to verify the presence of sex pheromones. The behavioral response of males was evaluated by bioassays using a Y-shaped-olfactometer containing a sample of female extracts. Analyzing the calling behavior, it was found that females of A. subrufella has only one calling position, and that this behavior has a peak between the second and fifth escotophases. Nor the duration of the calling or the number of calling bouts has changed over time, however, the beginning of the calling behavior was anticipated in older females, probably to avoid competition with younger females. Data showed that the best time to perform gland extractions and behavioral tests was between the third and seventh hour of the third or fourth escotophases. The chromatograms showed that it was not possible to demonstrate the presence of any female pheromonal compound, which was corroborated by the bioassays results, in which the male.s response did not indicate the presence of any pheromone. Thus, further studies are needed to elucidate the chemical structure of A. subrufella sex pheromone.